Performance of moringa (Moringa oleifera) and soil health under organic nutrition - B, MASTIHOLI A; B, BIRADAR I; B, GOPALI J; L, RUDRESH D; M, PRASANNA S (The Indian Journal of Agricultural Sciences, 2023)
A field trial was conducted during 2016–17, 2017–18, 2018–19 and 2019–20 at the Main Horticultural Research and Extension Centre, Bagalkot under Northern Dry Zone-3 of the Agroclimatic zones of Karnataka with an intention to study the response of moringa (Moringa oleifera L.) crop to different organic sources of nutrients. There were five nutrition treatments, viz. T1, 100% RDN through FYM; T2, 100% RDN through vermicompost; T3, 100% RDN through neem cake; T4, 1/3 RDN through FYM+1/3 RDN through vermicompost+1/3 RDN through neem cake and; T5, 50: 125: 30 kg NPK+20 tonnes FYM/ha (RDF) and replicated four times. The treatment T4 recorded significantly higher green pod yield (87.99 q/ha) which was on par with RDF (83.83 q/ha) and T3 (82.66 q/ha). However, most of the growth (except height) and yield contributing parameters, in all the organic treatments, were on par with RDF. Application of organic manures helped in improving available nutrients status, including micronutrients in soil. Among the different organic manures, the effect of FYM and VC in increasing the population of rhizosphere microorganisms was more than other treatments. Net return was found more in T4 (`124446/ha) followed by T3 (`118179/ha) and RDF (`114079/ha). It was found that organic manure applied in equal proportion (T4) and 100% substitution of N through neem cake (T3) was found better in getting higher yield and returns.